2018
DOI: 10.1007/s00405-018-5008-2
|View full text |Cite
|
Sign up to set email alerts
|

Provox 2® and Provox Vega® device life-time: a case-crossover study with multivariate analysis of possible influential factors and duration

Abstract: Results confirmed the non-significant differences on device life between Provox Vega and Provox 2, as well as the relevant role of radiotherapy treatment in the increase of replacements and diminution of the device duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 19 publications
6
15
1
Order By: Relevance
“…These data agree with the existing literature [2]. What's striking about the obtained results is the excellent mean device life-time (16 months), which is much higher than the one shown in the literature in general [3], as well as in the most recent articles [4,5] that place the cipher in 2-4 months. This is a fact that the authors themselves highlight in their own review.…”
Section: Letter To Editorsupporting
confidence: 91%
“…These data agree with the existing literature [2]. What's striking about the obtained results is the excellent mean device life-time (16 months), which is much higher than the one shown in the literature in general [3], as well as in the most recent articles [4,5] that place the cipher in 2-4 months. This is a fact that the authors themselves highlight in their own review.…”
Section: Letter To Editorsupporting
confidence: 91%
“…Comparing the most recent studies, authors reported that the median device life of the Provox Vega indwelling voice prosthesis is between 66 and 75 days. 3,4 The data found in our study do not differ in this sense. The most noteworthy of the results obtained is the mean lifetime achieved with the Provox XtraSeal, assuming an increase in more than two months without the need for replacement in patients with periprosthetic leakage compared to the Provox Vega, being the first work that studies and demonstrates this improvement.…”
Section: Discussioncontrasting
confidence: 45%
“…[8][9][10] In previous studies comparing two different generations of Provox, it had been shown that radiotherapy significantly affected the survival of the VP, being to a greater extent the Provox 2 than the Provox Vega. 3 The analysis performed in this study curiously finds the opposite in this cohort of patients. There seems to These findings support the use of Provox XtraSeal in patients with increased prosthesis replacements due to periprosthetic leakage, order to reduce the number of changes and therefore increasing the survival of VP.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations